Pragmatics Analysis On Conversation Between Close Friends In The Housing Environment - Uswatunnisa Uswatunnisa; Nihla Afdaliah; Afredy Krismahuddin (Interference: Journal of Language, Literature, and Linguistics, 2022)
This study aims to explain and describe (1) the content of pragmatics study in utterances in a conversation between two close friends; and (2) the intentions behind the conversation of two close friends who live in the Polewali Mandar district, Mapilli sub-district. This study used qualitative research methods. Data collection conducted by recording technique. The analysis technique was carried out using a narrative technique after the recording was made in a transcript file. The results of this study can be concluded as follows: (1) two close friends who converse with each other in their speech produce the content of many person and spatial deixis, references to things, speech acts, and the negative politeness in their speech (2) the intentions contained behind this conversation between two close friends are among others: to represent people and places, describing someone, asking for something without hesitation, expressing wishes directly and this conversation also takes floor that is never missed in a conversation with turn taking turns always goes on and backchannels always being given after giving an utterance, and adjacency pairs that always occur and are balanced, the answers always match with the questions.Keywords: Pragmatics, Conversation, Close Friends